Causes of poor math education in Iran and solutions for improving based on other countries experience - Kaboodvand, Tahereh; Mohd Ayub, Ahmad Fauzi (TextRoad Publication, 2013)
Mathematics learning disabilities (LD) have gained increased attention over the last decade from both researchers and practitioners Mathematic undoubted is one of the important courses which students need to know in all of the education stages. A large percentage of students receiving learning disability services experience difficulties with mathematics, but little research has examined the specific mathematics behaviors of students with LD who have teacher-identified math weaknesses. In this study, first we consider mathematics teaching in Iran and then propose solutions based on other countries experience. In general; there are various factors that prevent teaching and learning actively among students. Causes of math educational weakness relate to 3 categories : education ; students and book content solutions to improve each of them should be considered. A knowledgeable and active teacher should react to these factor before teaching then try to control preventive learning elements and provide essential motivation for active learning a money all of students.